The influence of the submergence ratio of submerged vanes on the slope of the hole around the pier groups in a sharp bend - Neda Safaripour; Mohammad vaghefi; Amin Mahmoudi (Journal of Hydraulic Structures)
Bridges are metal or concrete structures, which make road connections across rivers when installed over river paths. When flooding or scouring occurs, several issues including bridge destruction and interruption of road connections arise. There are a variety of methods of protecting such structures, one of which is application submerged vanes. This research shows how two vanes with different submergence ratio affected decrease in local scour surrounding one pier and groups of piers installed in a 180-degree bend. The scour around pier groups either in a transverse position to the flow or with a longitudinal direction was analyzed. This finding suggested that applying vanes decreased the deepest scour around the piers in all the tests, and its maximum effect occurred in triad longitudinal pier groups. By raising the submergence ratio, bed scour depth at the outer bank reached its minimum size in longitudinal pier groups. In transverse pier groups, the first scour hole near the outer bank increased in depth in the presence of vanes. By using the vanes, the slope of the scour hole towards the inner bank grew larger than that towards the other bank. The maximum slope of the outer bank happened in the triad transverse pier group at an approximate value of 0.63. The most significant impact of submerged vanes on reducing the upstream slope was observed in a single pier with 75% submerged vanes and triad longitudinal piers with 25% submerged vanes, resulting in reductions of about 50 and 74% respectively compared to piers without vanes.